Abdominal core training in windsurfing - Zhang, L. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: In Chinese windsurfing, it can be seen that although some coaches adopt relevant contents of abdominal core stability in their physical fitness training, such implementation does not perform its maximum potential on youngsters, mainly due to the lack of a specific protocol. Objective: Study the application of abdominal core stability training in windsurfing athletes. Methods: 14 young athletes in a windsurfing team were selected as volunteers and randomly divided into experimental control groups. A specially designed training protocol for abdominal center strengthening was added to conventional training for the experimental group. Fitness tests were performed, in both groups, before and after the intervention. The collected data were statistically analyzed and discussed. Results: The experimental group's 15m butterfly swim performance was improved by 0.25s, being 0.21s faster than the control group (P<0.05). Conclusion: The strengthening training protocol for the abdominal core stability presented in this study may improve the ability of windsurfing athletes, helping in dynamic and static balance.